Studies in law, politics, and society. Vol. 49 - Sarat, Austin (Emerald, 2009)
Trials are well known as paradigmatic legal events. Some attract wide attention; others mostly escape notice. Indeed in the United States trials have recently become rare, with some scholars bemoaning the death of the trial. This issue of "Studies in Law, Politics and Society" contains, along with two general interest articles, a symposium on the past, present, and future of the trial. It brings together the work of leading scholars to think about the nature, utility, and limits of trials. This work takes stock of the field, charts its progress, and points the way for its future development.
Keywords: Political sociology -- Research.; Political sociology -- Research -- United States.; Sociological jurisprudence -- Research -- United States.; Sociology -- Research -- United States.; Trial practice.; Practice of law.; Law & society.; Courts & procedure.; Law -- Trial Practice.; elektronické knihy; electronic books